A Study the Travel Writing of William Dalrymple Include in Xanadu: A Quest, City of Djinns: A Year in Delhi, THE Age of Kali: Indian Travels & Encounters: Uncovering hidden perspectives through Dalrymple's travel writings (Journal of Advances and Scholarly Researches in Allied Education, 2022)
William Dalrymple is a popular writer and art historian. He is known for his travelogues andhistorical narratives. He is also very active in the field of journalism. Dalrymple's best-known worksinclude In Xanadu A Quest (1989), City of Djinns A Year in Delhi (1993), The Age of Kali Indian Travels Encounters (1998). This proposed reading also studies these texts from the point of new historicismand subaltern historiography. Dalrymple’s texts are fine examples of multiple genres intersecting eachother. His works attract all kinds of readers whether they are lovers of history, romantic tales ortravelogues. He shifts his works between genres, modes, and medium, hence, the structure of his workbecomes very complex. His texts show an engagement with colonial discourses and his attempt torewrite history from a new perspective.